Linkages of Global Financial Crisis and Trade Direction in an Oil Based Economy - Al-Shammari, Nayef; Al-Obaid, Shaha (International Journal of Economics and Financial Issues, 2018)
This study examines the influence of the 2008 global financial crisis on trade flows between Kuwait and its main trading partners. Data sample covers the period from 1990 to 2012. In this study, estimates are tested using, fixed and random effects specifications, as well as Hausman test. Findings reveal that not all trading flows with Kuwait's trading partners got affected by the financial crises. Findings show that is the exports from Kuwait to China are affected Due to the financial crises. The expected negative influence of the global financial crisis is statistically significant in the case of Kuwait trade flows with China. Keywords: Financial Crisis, Gravity Model, Panel Approach, Kuwait. JEL Classifications: F21, O53, C1